PENGANGKATAN ANAK MENURUT HUKUM ADAT DITINJAU DARI UU NO. 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - SANIAH . (JURNAL ILMIAH MAKSITEK, 2022)
The institutions of child adoption have lived and developed for quite a long time in sosociety, the law that initially governed was customary law or local customary law. The procedure for adopting children also experiences dynamics along with the time. In addition to traditional law rules, adoption is currently regulated in law, namely law No. 23 of 2002 concerning Child Protection and Law No. 35 of 2014 concening Amendments to law No. 23 of 2002 concening Child Protection. Adoption regulated by law is based on the interests of the child to realize the child’s welfare and protection, in contrast to adoption based on customary law. This article concludes that the adoption of children subject to customary law is recognized by law.